APPLICATION OF BUSINESS INTELLIGENCE TECHNIQUES TO ANALYZE IT PROJECT MANAGEMENT DATA - Zachariah, Steffi; Khadakkar, Damini; Sharma, Vinay Kumar (IJRDO -Journal of Computer Science Engineering, 2017)
In today’s world web is the need of hour. Most of the crucial transactions and tasks are being done online in the form of web applications. Testing these web applications is an important task. Testing a web application manually is tedious, so there is a need to go for automation testing. In automation testing there is utilization of a product device to run repeatable tests against the application to be tried. There are various focal points of automation testing. There are various open source and business devices accessible for test mechanization. Selenium is one of the broadly utilized open source device for test computerization. Test automation enhances the effectiveness of programming testing procedures. Test automation gives quick criticism to engineers. It additionally discovers the imperfections when one may miss in the manual testing. In test automation we can perform boundless emphases for testing the same example of code ceaselessly commonly. The application of this tool can be seen in the automation of monthly allowance calculation of the employees of an organisation. Manually this tasks usually takes more than a week’s span but the use of Selenium IDE can reduce it upto a few hours.